A novel thermal regulation method for photovoltaic panels using porous metals filled with phase change material and nanoparticle additives. (July 2021) - Abdulmunem, Abdulmunem R.; Samin, Pakharuddin Mohd.; Rahman, Hasimah Abdul; Hussien, Hashim A.; Ghazali, Habibah
Abstract: The main problem with different types of PV cells is that they heat up beyond their optimal working temperature and thereby reduce their power generation efficiency. PV panel's thermal regulation utilising phase change material (PCM) has been a popular choice to counter the problem; however, the low thermal conductivity of PCMs is still an open challenge to fully exploit these materials as a potential solution. The effects of dispersing nanoparticles within the combination of PCM and copper foam matrix (CFM) on the PV panel performance was studied experimentally, under the climatic condition of Baghdad's city centre as a case study of a hot climate region. The results demonstrate the effect of the bundles of tangled tubes of the multi-walled carbon nanotubes (MWCNTs) additives with a 0.2% concentration ratio within the PCM/CFM, greatly improved the effective thermal properties of the material through the absorption and the rejection of heat. As a result, the electrical performance of the cells improves, which lead to an increase in the average electrical efficiency of the PV panel from 4% to 21% on the test day, when compared to the PV panels without passive cooling materials.